Five go to Billycock Hill - Blyton, Enid; Soper, Eileen Alice (Hodder Children's Books London, 1997)
"The Famous Five have made a new friend -- a pilot! But he has disappeared with top secret equipment. The Five can't believe it -- is Jeff a traitor?"--Page 4 of cover